The Influence of Board Characteristics on Earnings Management with Family Ownership as a Moderator - Mardianto, M.; Christian, Natalis; Joyslin, J. (Manunggal Halim Jaya, 2026)
This study examines the impact of family ownership and corporate governance mechanisms on earnings management practices, encompassing both accrual-based earnings management (AEM) and real-activity-based earnings management (REM). The independent variables include the board of commissioners (size, independence, meeting frequency, and expertise), the board of directors (size, independence, meetings, expertise), and company characteristics (size, leverage, growth). Data were sourced from companies listed on the Indonesia Stock Exchange (IDX), utilizing annual financial reports or annual reports spanning the period from 2017 to 2023, excluding the financial and banking sectors. Analysis was performed employing multiple regression and moderation regression models. The findings of this study show that family ownership has a significant effect on both AEM and REM, while several corporate governance variables and company characteristics have varying effects. These findings have important implications for regulators, investors, and company management to strengthen the transparency and accountability of financial reporting.